Who Contracts? Determinants of the Decision to Work as an Independent contractor among Information Technology Workers - Bidwell, Matthew J.; Briscoe, Forrest (Academy of Management Journal, 2009)
We examined which IT workers take jobs as independent contractors. Contracting offers less job security and less employer-provided training than regular employment. We base our predictions of which workers contract on how their preferences and resources match such jobs. Using career history data, we found that the likelihood of contracting increases with skill levels and presence of negative cues, and falls (for men) with family responsibilities. Contracting is more likely among workers whose careers are either just beginning or well advanced; the latter group also remains in contracting longer. These findings have implications for benefits, skills development, and income security policies.